Camera trapping reveals habitat overlap between snow leopards and common leopards in Gaurishankar Conservation Area, Nepal. : Habitat overlap between snow leopards and common leopards in Gaurishankar Conservation Area, Nepal
We provide camera trap records of the presence of two large predators: the snow leopard Panthera uncia and common leopard Panthera pardus from the same habitats in Lapchi Valley of Gaurishankar Conservation Area. Camera traps were laid for 2,304 (mean 88.62 Å